Pembudayaan Karakter Nasionalis dan Integritas di SDN 3 Kaliawi Bandar Lampung - Yulia Siska; Hendra Saputra; Hayatil Hasanah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
This study aims to determine the implementation of character education at SDN 3 Kaliawi in cultivating the strengthening of nationalist character and integrity in schools. This research is a descriptive study with a qualitative approach that seeks to reveal in depth the findings of the existing data based on the data to be presented and interpreted. Data collection was carried out under natural conditions, primary data sources and data collection techniques were dominated by in-depth interviews, observation, and documentation. The qualitative data analysis technique used is interactive analysis. The results showed that the implementation of character education through school culture was integrated in intracurricular and extracurricular activities. Character values ​​that can be formed through school culture are nationalism and integrity. The obstacles encountered in the process of cultivating character values ​​in schools are the lack of attention of parents to students and a less conducive environment. While the solutions to overcome the problem of implementing KDP based on school culture are: 1) attention to students; 2) socialization to parents; and 3) mutual respect.